2016
DOI: 10.1111/jgs.14661
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Klotho with Loss of Bone Mineral Density and Fracture Risk in Older Adults

Abstract: OBJECTIVES Klotho deficiency has been previously linked to aging-like phenotypes such as osteoporosis, cognitive impairment, and sarcopenia. Low serum klotho was shown to be related to grip strength and disability. Nonetheless, no previous study has explored the association between serum klotho and fractures. The purpose of this report is to examine the relationship of serum klotho with bone mineral density (BMD) loss and fractures in older adults. DESIGN The Health, Aging, and Body Composition (Health ABC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Nevertheless, more research is needed because until now, only a few cross-sectional studies have investigated the association of FGF23 with BMD in apparently healthy participants, providing controversial results [ 59 , 60 , 61 , 62 ]. Furthermore, until now, only a few epidemiological studies [ 60 , 63 , 64 ] have investigated the associations between circulating α-klotho and bone health and showed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more research is needed because until now, only a few cross-sectional studies have investigated the association of FGF23 with BMD in apparently healthy participants, providing controversial results [ 59 , 60 , 61 , 62 ]. Furthermore, until now, only a few epidemiological studies [ 60 , 63 , 64 ] have investigated the associations between circulating α-klotho and bone health and showed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In the CKD patients, Klotho protein did not correlate with bone density. Chalhoub et al showed no correlation between Klotho, BMD and the risk of bone fracture [31]. Yaghoubi et al showed no significant correlation between FGF23, BMI and lipid profile [32].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given the central role of klotho in calcium/ phosphate balance and in bone remodelling, the regular intake of calcium and cholecalciferol in 20 osteoporotic patients and the lack of a control group could have added further bias to our analysis, although no significant association was recorded between serum klotho concentration and the odds of having osteoporosis in the SSc cohort. Moreover, a recent work by Chalhoub et al failed to assign sufficient relevance to soluble klotho as a biomarker of bone resorption and fracture risk (25). …”
Section: Original Papermentioning
confidence: 99%